1981
DOI: 10.1113/jphysiol.1981.sp013804
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sodium ion activity and sodium transport in rabbit urinary bladder.

Abstract: SUMMARY1. Intracellular potentials and the intracellular activities of Na+ and K+ were examined using conventional and ion-selective micro-electrodes.2. In animals on a normal diet, the intracellular Na+ activity was 8-6 + 2-9 mM (mean + S.D.) with a mean short-circuit current of 2-8 + 09 ,uA/cm2.3. In animals on a low-Na+ diet, the intracellular Na+ activity was 185 + 9-9 mM with a short-circuit current of 4-5+13 ItA/cm2 (mean+ S.D.).4. There was a correlation between short-circuit current and intracellular N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 38 publications
(59 reference statements)
6
39
2
Order By: Relevance
“…Such a stoichiometry is not unusual and has been reported in other epithelia using radiotracer and electrical methodology (Nielsen, 1979;Zeuthen & Wright, 1981;Kirk, Halm & Dawson, 1980;Eaton, 1981;Hviid Larsen, Fuchs & Lindemann, 1979).…”
Section: Pump Stoichiometrymentioning
confidence: 84%
See 1 more Smart Citation
“…Such a stoichiometry is not unusual and has been reported in other epithelia using radiotracer and electrical methodology (Nielsen, 1979;Zeuthen & Wright, 1981;Kirk, Halm & Dawson, 1980;Eaton, 1981;Hviid Larsen, Fuchs & Lindemann, 1979).…”
Section: Pump Stoichiometrymentioning
confidence: 84%
“…The work of Eaton and co-workers (Eaton, 1981, Eaton, Frace & Silverthorn, 1982) indicates a 3:2 stoichiometry for the basolateral pump of the rabbit urinary bladder. We find this value is in good agreement with our electrical measurements.…”
Section: Pump Stoichiometrymentioning
confidence: 99%
“…1,2 It has been suggested that the urothelium can mediate water and solute transport under certain circumstances. [3][4][5] Several studies have shown that the urinary bladder epithelium contains a sodium transporter 6 that has been identified as an epithelial sodium channel (ENaC), 7 which is known to be responsible for salt and fluid transport across the epithelia of many tissues. 8 Aquaporins (AQPs) are a family of intrinsic membrane proteins that function as water channels in many cell types involved in fluid transport.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, significant net transport (both lumen to blood and blood to lumen) of solutes, including urea, creatinine, sodium, potassium, and chloride, usually down their respective blood/urine gradients, has been demonstrated in vivo in rabbits and rats and studies of perfused dog ureter (14,29) and bladder (8,9,14,21,27). Furthermore, a number of studies have shown that rabbit and guinea pig urinary bladder epithelium contain an aldosterone-stimulated, amiloride-inhibited sodium transporter (2,16), which has recently been identified by Northern blot analysis as the epithelial sodium channel (22). The epithelial sodium channel is known to be responsible for salt and fluid transport across epithelia of many tissues (6).…”
mentioning
confidence: 99%